THE MEASUREMENTS OF BALANCED SCORECARD TO SUPPORT PLANNING AND MANAGEMENT PERFORMANCE IMPROVEMENT AT UB GUEST HOUSE MALANG - Pongsapan, Marchelyn (Jurnal Ilmiah Mahasiswa FEB, 2017)
Perforance   measurement  is  a  measurement  used   to   help   improve  a company's   management   performance.   In  2014   -   2015   UB   Guest   House experienced  a  decrease in  management  performance  therefore  this  study  aims to measure  the  performance  of UB  Guest  House  as  a  whole not  only in terms of financial  but  in  terms  of  non-financial  so  it  can  be  used  as  a  benchmark  in planning  and improving  activityy  in  UB  Guest  House  Malang  continuously. This research is quantitative descriptive research and  uses field  research or observation techniques  to  collect  data.The primary  data  is  in  the  form of questionnaire  and explained by Balamced Scorecard (BSC). From the analysis result using four perspectives  in  Balanced  Scorecard,  it  showed  that  overall  UB  Guest  House performs well and has a balance performance.Keywords: Balanced  Scorecard,  Financial Perspective,  Customer Perspective, Internal Business Perspective, Growth Perspective and Learning.